Interviews - Matt, Gerald; Aparicio, Eduardo; Bareikis, Aidas; Barney, Matthew; Beecroft, Vanessa; Breitz, Candice; Bruguera, Tania; Cai Guo-Qiang; Cantor, Ellen; Chicks on Speed; Cohen, Steven; Deutschbauer, Julius; et al. (Köln Wien : Kunsthalle Wien, 2007)
Aparicio, Eduardo ; assume vivid astro focus ; Bareikis, Aidas ; Barney, Matthew ; Beecroft, Vanessa ; Breitz, Candice ; Bruguera, Tania ; Cai Guo-Qiang ; Cantor, Ellen ; Chicks on Speed ; Cohen, Steven ; Deutschbauer, Julius ; Djuric, Uros ; Hirakawa, Noritoshi ; Islam, Runa ; Jermolaewa, Anna ; Julien, Isaac ; Kim, Soo-Ja ; Krystufek, Elke ; Kusolwong Surasi ; Landau, Sigalit ; Lin, Michael ; Magema, Michèle ; Margolles, Teresa ; Matelli, Tony ; McQueen, Steve ; Medoune Seye, Bouna ; Moffatt, Tracey ; Neshat, Shirin ; Onofre, João ; Pettibon, Raymond ; Pope.L, William ; Riello, Antonio ; Sala, Anri ; Schinwald, Markus ; Sierra, Santiago ; Spring, Gerhard ; Tomic, Milica ; Vezzoli, Francesco ; Wong Hoy Cheong ; Yang Fudong
boek